2004
DOI: 10.1177/0265407504047838
|View full text |Cite
|
Sign up to set email alerts
|

A model of relational turbulence: The role of intimacy, relational uncertainty, and interference from partners in appraisals of irritations

Abstract: The development of romantic relationships is a complex process by which previously autonomous individuals come to perceive themselves as a social unit. We propose that the transition from casual dating to serious involvement coincides with relational turbulence in courtship, and we identify relational uncertainty and interference from partners as mechanisms that may explain why this turmoil occurs. We test our model by examining people’s appraisals of irritating circumstances as a marker of relational turbulen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
382
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 277 publications
(401 citation statements)
references
References 39 publications
16
382
2
1
Order By: Relevance
“…Other researchers have reported on the importance of assessing intimacy in this way (Santore, 2008;Schwebel et al, 1999). Because both theory and empirical data support a linear increase in levels of intimacy (Solomon & Knobloch, 2004), we expected to find the same pattern. Unique to our study is the focus on conflict strategies rather than frequency of conflict or negative emotions.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…Other researchers have reported on the importance of assessing intimacy in this way (Santore, 2008;Schwebel et al, 1999). Because both theory and empirical data support a linear increase in levels of intimacy (Solomon & Knobloch, 2004), we expected to find the same pattern. Unique to our study is the focus on conflict strategies rather than frequency of conflict or negative emotions.…”
mentioning
confidence: 60%
“…First, Solomon, and Knobloch (2004) found empirical support that levels of intimacy increased over time (linear increase). In addition, Aune, Aune, and Buller (1994) found that romantic partners in relationships of moderate duration reported expressing the most negative emotions.…”
mentioning
confidence: 97%
“…Relational turbulence arises when changes in a relationship give rise to increased reactivity to relationship conditions (Solomon & Knobloch, 2004), which can manifest as intensified emotional, cognitive, or communicative reactions to relationship circumstances (Solomon, Weber, & Steuber, 2010). According to the model, two interrelated mechanisms give rise to relational turbulence: relational uncertainty and interference from partners.…”
Section: Relational Turbulence and The Empty-nest Phase Of Marriagementioning
confidence: 99%
“…In other circumstances, however, interference from partners tends to promote more assertive communication behavior. For instance, interference from a partner is associated with perceptions of relationship problems as more severe and relationally threatening, which promotes more direct confrontations about relationship issues (Solomon & Knobloch, 2004;Theiss & Solomon, 2006b). In addition, dating partners tend to be disaffiliative in their messages to one another when interference from partners is high (Knobloch, 2006).…”
Section: Features Of Conflict Interaction As Markers Of Relational Tumentioning
confidence: 99%
See 1 more Smart Citation